Evaluation of Seed Oil, Protein Content and Fatty Acid Composition in Sesame Accessions in the Northern Fertile Crescent, Turkey - KARAASLAN, DAVUT (Asian Journal of Chemistry, 2010)
35 Cultivated sesame accessions were analyzed in the Northern Fertile Crescent. The stability in the seed protein and oil content as well as the fatty acid composition and the relationship between the oil content and the specific fatty acids were investigated. Hence, correlations among fatty acids on oil content were analyzed to obtain an explanation of their interrelationships for the future breeding program. Significant differences were observed between accessions for the oil content and the correlations between the fatty acids (p < 0.01). The palmitic acid and oleic acids negatively correlated with linoleic, linolenic and arachidic acids. After some additional analysis in different locations of experimantal study, several accessions tested in this study were used as parental lines for the future breeding programs.